Housing Collateral, Consumption Insurance, and Risk Premia: An Empirical Perspective - LUSTIG, HANNO N.; VAN NIEUWERBURGH, STIJN G. (Journal of Finance, 2005)
ABSTRACT In a model with housing collateral, the ratio of housing wealth to human wealth shifts the conditional distribution of asset prices and consumption growth. A decrease in house prices reduces the collateral value of housing, increases household exposure to idiosyncratic risk, and increases the conditional market price of risk. Using aggregate data for the United States, we find that a decrease in the ratio of housing wealth to human wealth predicts higher returns on stocks. Conditional on this ratio, the covariance of returns with aggregate risk factors explains 80% of the cross‐sectional variation in annual size and book‐to‐market portfolio returns.